An efficient process to synthesize solketal from glycerol over tin (II) silicotungstate catalyst. (1st December 2020) - da Silva, Márcio Jose; Teixeira, Milena Galdino; Chaves, Diego Morais; Siqueira, Lucas
Graphical abstract: Highlights: We report that Sn2 SiW12 O40 salt act as Lewis and Brønsted acid catalyst. Sn2 SiW12 O4 was most active than Keggin HPAs and tin(II) salt catalysts. Catalyst concentration was a key aspect to control the reaction selectivity. A simple procedure allowed recovery the acetone and recycle the Sn2 SiW12 O40 . Abstract: In this work, Sn(II)-exchanged silicotungstic acid salt (i.e., Sn2 SiW12 O40 ) was synthesized and evaluated as the catalyst on the acetalization of glycerol with acetone to produce solketal, a versatile bioadditive of fuel. The Sn2 SiW12 O40 salt was compared to the other solid Keggin heteropoly salts (i.e., Sn3/4 PMo12 O40, Sn3/4 PW12 O40 ), and liquid (i.e., HCl, H2 SO4 and p -toluenesulfonic acid) catalysts. Amongst the catalysts assessed, it was the most active, achieving a high conversion (ca. > 99%, after 1 h reaction at room temperature) and selective (ca. 97%) toward the formation of solketal. Moreover, the Sn2 SiW12 O40 salt demonstrated to be more active than acid and precursor Tin (II) chloride salt, as well as other heteropoly salts and solid supported catalysts. The effects of the main reaction variables were assessed. The Sn(II) cation, as well as the silicotungstate anion, showed being essential to convert glycerol to solketal. Insights on the reaction mechanism were performed. In a simple recycle procedure, the solketal was purified, the acetone excess recycled, and the catalyst was reused without loss activity.